Optimizing Treatment of Oil Palm-Empty Fruit Bunch (OP-EFB) Fiber: Chemical, Thermal and Physical Properties of Alkalized Fibers - Abdullah, Che Ibrahim; Azzahari, Ahmad Danial; Abd Rahman, Nor Mas Mira; Hassan, Aziz; Yahya, Rosiyah (Springer Verlag, 2019)
Oil-palm empty fruit bunch (EFB) is a waste matter that is abundantly generated from the oil palm industries. Natural fibers derived from this lignocellulosic biomass have the potential to be used as reinforcement material in polymer composites as a greener alternative to synthetic fibers. However, some treatment has to be done to overcome inherent disadvantages in natural fibers and further improve its properties. One such method to prepare the fibers for chemical modification is by alkalization. In this study the EFB fibers were immersed in sodium hydroxide (NaOH) solution with concentrations and immersion times varied to 4, 8 and 12 w/v % and 6, 12, 24 and 48 h, respectively. The EFB fibers were characterized using FTIR, TGA, XRD, FE-SEM, diameter profiling and mechanical tests. Results from FTIR showed that the treated EFB have significant increment of intensity at 3335 cm-1 corresponding to -OH groups. Optimum treatment conditions for the EFB fibers were found at 4 w/v% NaOH and 24 h. Diameter profiling showed better uniformity in the treated EFB fibers with improved tensile properties. © 2019, The Korean Fiber Society.